2009
DOI: 10.1128/aac.01655-08
|View full text |Cite
|
Sign up to set email alerts
|

β-Lactamase-Mediated β-Lactam Resistance in Campylobacter Species: Prevalence of Cj0299 ( bla OXA-61 ) and Evidence for a Novel β-Lactamase in C . jejuni

Abstract: Fifty-two percent of 1,288 poultry isolates of campylobacters were ampicillin resistant, and resistance was more common among Campylobacter coli isolates (67.4%) than among Campylobacter jejuni isolates (47.5%). Production of ␤-lactamase was typically associated with resistance to ampicillin, amoxicillin (amoxicilline), penicillin, and ticarcillin. Regardless of ␤-lactamase production, all isolates were resistant to piperacillin (MICs > 256 g/ml), and most were resistant to carbenicillin, cloxacillin, and ceph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
66
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 25 publications
6
66
0
Order By: Relevance
“…Recently, it was proposed that an oral β-lactam may provide an alternative therapy, although epidemiological studies have shown β-lactam resistance to be commonly observed in Campylobacter spp. (Griggs et al 2009, Gormley et al 2010). β-lactam antimicrobials, which inhibit bacterial cell wall biosynthesis, have been the most commercially available antimicrobials in the market because of their high specificity and potent killing effect (Zeng et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was proposed that an oral β-lactam may provide an alternative therapy, although epidemiological studies have shown β-lactam resistance to be commonly observed in Campylobacter spp. (Griggs et al 2009, Gormley et al 2010). β-lactam antimicrobials, which inhibit bacterial cell wall biosynthesis, have been the most commercially available antimicrobials in the market because of their high specificity and potent killing effect (Zeng et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…S3), with only seven polymorphic sites among 774 nucleotides. This gene, which encodes a characterized enzyme called bla OXA-61 conferring resistance to β-lactam antibiotics (12), was found at the highest frequency in cattle isolates and was rarest in isolates from wild birds (Fig. S1).…”
Section: Resultsmentioning
confidence: 99%
“…Three upstream genes (surE, Cj0294, and Cj0295) are also involved in biosynthesis. Immediately downstream is an ampicillin resistance-associated gene, bla OXA-61 (12), which is also associated with cattle. The gene is notable for being the least diverse of the common genes in the Campylobacter genome (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To address this issue, we first constructed an E. coliCampylobacter shuttle vector (pZW) ( Table 1) carrying a Campylobacter promoter according to the procedure described by Larsen et al (8). The two selected novel AR gene products (FRAmp1.1, conferring ampicillin resistance, and FRSpe1.1, conferring spectinomycin resistance) shared low sequence similarity to the major determinants of ampicillin resistance (Cj0299) and spectinomycin resistance (AadA) in Campylobacter (6,17). FRAmp1.1 and FRSpe1.1 were PCR amplified using proper primers pairs (Table 2), and the PCR fragments were cloned into pZW, creating pZW1 and pZW2, respectively.…”
mentioning
confidence: 99%